Discontinuous and non-discontinuous subgenomic RNA transcription in a nidovirus - van Vliet, A.L.W. (Oxford University Press, 2002)
Arteri-, corona-, toro- and roniviruses are evolutionarily related positive-strand RNA viruses, united in the order Nidovirales. The best studied nidoviruses, the corona- and arteriviruses, employ a unique transcription mechanism, which involves discontinuous RNA synthesis, a process resembling similarity-assisted copy-choice RNA recombination. During infection, multiple subgenomic (sg) mRNAs are transcribed from a mirror set of sg negative-strand RNA templates. The sg mRNAs all possess a short 5′ common leader sequence, derived from the 5′ end of the genomic RNA. The joining of the non-contiguous ‘leader’ and ‘body’ sequences presumably occurs during minus-strand synthesis. To study whether toroviruses use a similar transcription mechanism, we characterized the 5′ termini of the genome and the four sg mRNAs of Berne virus (BEV). We show that BEV mRNAs 3–5 lack a leader sequence. Surprisingly, however, RNA 2 does contain a leader, identical to the 5′-terminal 18 residues of the genome. Apparently, BEV combines discontinuous and non-discontinous RNA synthesis to produce its sg mRNAs. Our findings have important implications for the understanding of the mechanism and evolution of nidovirus transcription.